2007
DOI: 10.1111/j.1751-1097.2007.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Fluorescence Dominates UV Photoemission of Folded Cytochrome c

Abstract: In this article we reinvestigate the bimodal fluorescence of cytochrome c (Cyt c) by using excitation-wavelength-dependent fluorescence spectroscopy. We show that its major contributions at pH 3-7 do not arise from tryptophan (Trp-59) fluorescence as hitherto assumed. Instead, different chromophores of Cyt c contribute at different pH values. At pH 3-7, the porphyrin system contributes about 80% and tryptophan about 20% to the total fluorescence upon excitation of Cyt c at 280 nm. At pH 2, the fluorescence ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…This delayed haem population, also observed in its emission (see section 3), is concomitant with the Trp de-excitation and provides unambiguous evidence of a very efficient Trp-haem energy transfer, on the time scales of 350 and 700 fs. This is also in agreement with fluorescence QY measurements as a function of pH, , if we compare them to the radiative decay of ∼3 ns measured in aqueous solution …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This delayed haem population, also observed in its emission (see section 3), is concomitant with the Trp de-excitation and provides unambiguous evidence of a very efficient Trp-haem energy transfer, on the time scales of 350 and 700 fs. This is also in agreement with fluorescence QY measurements as a function of pH, , if we compare them to the radiative decay of ∼3 ns measured in aqueous solution …”
Section: Discussionsupporting
confidence: 87%
“…The UV fluorescence emission of Cyt c (300–450 nm) is expected to stem mainly from Trp residue. ,,, However, Löwenich et al reported a bimodal fluorescence, investigated through excitation-wavelength-dependent fluorescence spectroscopy . They claimed that upon excitation at 280 nm and at pH 7, the iron porphyrin contributes about 80% and tryptophan about 20% to the total fluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…35 The unfolding upon increasing urea concentration is characterized by a cooperative transition, N ↔ U, between the native (N) and unfolded conformations (U). 40 This equilibrium has been extensively characterized by different techniques including fluorescence 41 and circular dichroism (CD). 35,42 The stability of cyt c was accordingly analyzed here under the assumption of a simple N ↔ U equilibrium.…”
Section: Biomacromoleculesmentioning
confidence: 99%